Tyrosine phosphorylation of the insulin receptor is not required for receptor internalization: studies in 2,4-dinitrophenol-treated cells. - Backer, J M (1989)
The relation between insulin-stimulated autophosphorylation of the insulin receptor and internalization of the receptor was studied in Fao rat hepatoma cells. Treatment of Fao cells with 2,4-dinitrophenol for 45 min depleted cellular ATP by 80% and equally inhibited insulin-stimulated receptor autophosphorylation, as determined by immunoprecipitation of surface-iodinated or [32P]phosphate-labeled cells with anti-phosphotyrosine antibody. In contrast, internalization of the insulin receptor and internalization and degradation of 125I-labeled insulin by 2,4-dinitrophenol-treated cells were normal. These data show that autophosphorylation of the insulin receptor is not required for the receptor-mediated internalization of insulin in Fao cells and suggest that insulin receptor recycling is independent of autophosphorylation.